Endocannabinoid System and Cannabinoid 1 Receptors in Patients With Pharmacoresistant Temporal Lobe Epilepsy and Comorbid Mood Disorders - Rocha, Luisa; Cinar, Resat; Guevara-Guzmán, Rosalinda; Alonso-Vanegas, Mario; San-Juan, Daniel; Martínez-Juárez, Iris; Castañeda-Cabral, José Luis; Carmona-Cruz, Francia (Frontiers in Behavioral Neuroscience, 2020)
Experimental evidence points out that activation of endocannabinoid system induces neuroprotective effects and reduces mood disorders. In the hippocampus of patients with mesial temporal lobe epilepsy (MTLE), studies indicated augmented Cannabinoid 1 receptor (CB1R) binding, in spite of its low mRNA and protein expressions. Although this situation suggests an enhanced CB1R-induced neurotransmission in patients with MTLE, especially those with pharmacoresistant seizures, which present important neuronal damage and high comorbid mood disorders. The present study focused to investigate the status of CB1R and endocannabinoid system by obtaining CB1R-induced G-protein signaling efficacy and measuring the tissue levels of endocannabinoids in hippocampus and temporal neocortex of patients with pharmacoresistant MTLE. Furthermore, the obtained results were correlated with comorbid anxiety and depression. The experiments revealed that patients with MTLE present increased CB1R-induced G-protein signaling efficacy (Emax) as well as augmented tissue content of anandamide (AEA) and oleoylethanolamine (OEA), and low 2-Arachidonoylglycerol (2-AG). Some of these changes were more evident in patients with MTLE without mood disorders. The current findings indicate that pharmacoresistant MTLE is associated with increased CB1R-induced transductional mechanisms as well as augmented tissue content of specific endocannabinoids in hippocampus and temporal neocortex. The enhanced endocannabinoid neurotransmission may be involved in the absence of comorbid mood disorders in some patients with MTLE.